Haode Evaluating the Life-cycle Environmental Impacts of Polyester Sports T-shirts. Issue 2 (April 2020) - Wu, Zequan
Abstract: Polyester fibre has a series of excellent properties and it has a wide range of uses. Recently China has become the largest producer and consumer of polyester in the world. The purpose of this paper is to analysis the environmental impacts of polyester shirts. Applying life cycle assessment to polyester textiles, through the analysis and research of resource utilization and environmental emissions during the life of polyester textiles, looking for opportunities to reduce environmental pollution, and providing reference for environmental management departments to develop environmental regulations and environmental emission reduction plans. The declared unit of this paper is a piece of T-shirt 100% made of polyeater fibre. Following the principles and guidelines of ISO series, this study collected both measured data of the client's processes and secondary data. The data in this paper mainly comes from the literature, life cycle assessment (LCA) databases, and emission registration database of the government. The results of the study show that PET production, yarn manufacturing, and use-phases are the procedures that contribute the most environmental impacts. The total life-cycle energy use of a polyester sports shirt is 109 MJ, with 2882 litres of cumulative water use and contribution to global warming equivalent to 81.62 kg of CO2. The shirt's use phase contribute the highest resources used, accounting for 65.5% of energy use, 86.71% of water use, and 84.31% of the global warming potential. The shirt production phase accounts for 30.85% of the energy use, 13.14% of total water use, and 12.99%of the global warming potential. Disposing phase contribute less among these process. The results of the study show that PET production, yarn manufacturing, and use-phases contributes to the majority of all environmental impacts. Polyester production and yarn manufacturing are steps that require the highest amount of energy. Utilizing recycled polyester fibres can reduce the net resource utilization and environmental impacts. A large amount of energy and water are used in the use-phase of a shirt. Improving the equipment efficiency can decrease the input energy and water consumption.